PENGAWASAN TEMPAT KARAOKE OLEH SATUAN POLISI PAMONG PRAJA KOTA PEKANBARU - Ardiansyah, Dista Khoesnul; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In an affort to curb the place of entertainment, the government of pekanbaru city make local regulation, number 03 of 2002 about general entertainment, one of which is karaoke place. the suvervisor of karaoke aims to curb the place of karaoke so that in the implementation of this business operations do not make a disadvantage, a danger, and disturbance to the society and surrounding environment. Based on the experience of research in field, most place of karaoke do not comply with local regulation that made by government of pekanbaru city. The purpose of this research is to know how the surveillance of karaoke place by Civil Service City Force of Pekanbaru and to know the factors that affect surveillance karaoke place in pekanbaru city. This research conducted in Pekanbaru city with using qualitative descriptivr method, with collect data through observation and interviews. this research done by using theory of Manullang, which set the standards, make an assesment snd take correctivr action. The result ot this research conclution, supevision by Civil Service City Force of Pekanbaru still not implemented effectively, this is proven by the many of karaoke place that still dilo not comply with the rules that made by government of Pekanbaru city. this happend because of government do not serious in supervission, do not maximal in implementation the rules. and sosialitation for the own karaoke busines in Pekanbaru do not maximal. Keyword : Supervision, Entertainment, Management